2016
DOI: 10.1186/s13049-016-0243-2
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the views of paramedics regarding airway management

Abstract: BackgroundParamedics are a skilled group of clinicians with expertise in airway management. Our research group has completed a trial comparing supraglottic airway devices with tracheal intubation during out of hospital cardiac arrest. This is a contentious topic amongst paramedics in the United Kingdom (UK). We explored the customs and beliefs of UK paramedics in relation to airway management, and whether tracheal intubation contributes to and sustains paramedic professional identity.MethodsThe study took plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…Participation in research was seen as consistent with their professional identity as modern and effective health care providers, yet threatened this very identity if negative results ensued. This finding is consistent with previous studies of paramedic involvement in prehospital research, and is an important aspect to consider …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Participation in research was seen as consistent with their professional identity as modern and effective health care providers, yet threatened this very identity if negative results ensued. This finding is consistent with previous studies of paramedic involvement in prehospital research, and is an important aspect to consider …”
Section: Discussionsupporting
confidence: 92%
“…JVVF and JB work as emergency medicine and prehospital physicians, and have published largely quantitative research with an underlying positivist epistemology . JBR is a research fellow who has focused on qualitative research in a variety of health care settings and has previously worked with JB on a qualitative study in prehospital care . This exploration of stakeholders' views of prehospital critical care for OHCA is nested within a quantitative analysis of the effects of this complex intervention on survival after OHCA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study on the topic16 and indeed qualitative studies looking at paramedics practice more generally (eg,68–70) have recruited from only single sites. Paramedics for this study were recruited from five different services and so it is likely the issues reported do not relate to isolated, local concerns, but reflect practice across the country.…”
Section: Discussionmentioning
confidence: 99%
“…This categorization was chosen because airway control has the highest treatment priority in emergency medicine, is considered the single most important factor for good outcomes, 30,31 and contributes to paramedics' professional identity. 32 In this study, crewmembers unavailable to assist the medical crew in patient treatment during flight were not included as part of the medical crew. Nurses and EMTs/paramedics with a combined role as a medical assistant and a pilot's assistant during flight and obliged to sit in the cockpit under normal flight operations were categorized as an HEMS crewmember (HCM).…”
Section: Definitions and Classificationsmentioning
confidence: 99%